1992
DOI: 10.1149/1.2069205
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lithographic Patterning on Current Distribution: A Model for Microfabrication by Electrodeposition

Abstract: A model has been developed to predict current distribution in electrodeposition onto substrates that contain lithographic patterns. The aim of the work was to understand the strong effects that substrate patterning can exert on the thickness distribution of plated films. Based on the familiar potential-theory model for secondary current distribution in electrochemical cells, the model is applicable at length scales that are large compared to the individual features of a pattern. The pattern is described entire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 17 publications
0
54
0
Order By: Relevance
“…These effects need to be minimized in order to achieve uniform, flat shapes and reproducible material properties. At the pattern scale, it was found that a higher average current density is obtained in regions having a low density of patterns to be filled [19], as schematically shown in Figure 28.5. Design rules for MEMS thus suggest that the pattern should have a uniform density of features of similar size [20].…”
Section: Characteristic Features Of Electrodeposition Through High-armentioning
confidence: 88%
“…These effects need to be minimized in order to achieve uniform, flat shapes and reproducible material properties. At the pattern scale, it was found that a higher average current density is obtained in regions having a low density of patterns to be filled [19], as schematically shown in Figure 28.5. Design rules for MEMS thus suggest that the pattern should have a uniform density of features of similar size [20].…”
Section: Characteristic Features Of Electrodeposition Through High-armentioning
confidence: 88%
“…pattern being plated [38,39]. In 1969, however, the required mathematics was not available, and even if it were, the modeling would have required a lot of expensive computer time on a main frame system.…”
Section: Through-mask Platingmentioning
confidence: 99%
“…Wafer-to-wafer repeatability is very important in order to ensure uniform product characteristics, and within-die or within-feature thickness or alloy composition uniformity may also be critical factors. Some of these considerations mean that the microscale pattern density of the substrate may be important in terms of determining the results on the wafer or substrate [37][38][39].…”
Section: Wafer Plating Equipmentmentioning
confidence: 99%